Quantitative Analysis of Myocardial Work by Non-invasive Left Ventricular Pressure-Strain Loop in Patients With Type 2 Diabetes Mellitus - Huang, Danqing; Cui, Cunying; Zheng, Qiang; Li, Yanan; Liu, Yuanyuan; Hu, Yanbin; Wang, Ying; Liu, Ruijie; Liu, Lin (Frontiers in Cardiovascular Medicine, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a common risk factor for cardiovascular diseases. The aims of this study were to evaluate the changes in the left ventricular myocardial work in T2DM patients using the left ventricular pressure-strain loop (PSL) technique, and to explore the risk factors for the left ventricular myocardial work impairment. Methods: Fifty patients with T2DM and 50 normal controls (NCs) were included in the study. In addition to conventional echocardiography and two-dimensional speckle tracking echocardiography, the left ventricular myocardial work parameters were measured using PSL technology. Results: The absolute value for global longitudinal strain (GLS), global work index (GWI) and, global constructive work (GCW) were significantly decreased in the T2DM group (P < 0.05), while the left ventricular ejection fraction (LVEF) was not significantly different between the T2DM and NC groups. Multivariable linear regression analysis showed that hemoglobin A1c (HbA1c) was independently related to GWI (β = −0.452, P < 0.05), while HbA1c and the diabetes duration were independently related to GCW (β = −0.393, P < 0.05 and β = −0.298, P < 0.05, respectively). Conclusions: Changes in the left ventricular myocardial systolic function in T2DM patients were identified using PSL technology. HbA1c was shown to be an independent risk factor affecting GWI, while HbA1c and diabetes duration were demonstrated to be independent risk factors affecting GCW.